Factors associated with in-hospital mortality of newborns admitted to a special care newborn unit of a tertiary care hospital in southern Bangladesh: a retrospective cohort study - Md Mostafizur Rahman; Tahmina Zerin; Md Abdullah Saeed Khan; Md Golam Abbas; Aysha Haque; Mohammed Zahidul Alam; Ummay Thamima; Md Wahiduzzaman; Siddhartha Sankar Das (BMJ Open)
Objectives The objective of this study was to identify factors associated with in-hospital deaths of newborns admitted to a special care newborn unit (SCANU) in southern Bangladesh.Design Retrospective cohort.Setting SCANU of Patuakhali Medical College Hospital, Patuakhali, Bangladesh.Participants Records of 930 neonates admitted to the SCANU from August to December 2022 were included in the study. The inclusion criteria consisted of neonates admitted during the specified period, while the exclusion criteria excluded records of newborns who were referred to intensive care units or who left against medical advice.Primary and secondary outcome measures Primary outcome: In-hospital neonatal mortality. Secondary outcomes: Specific conditions or factors affecting the in-hospital deaths.Results Of the 930 neonates analysed, 3.44% died in the hospital. Factors significantly associated with shorter survival time and increased in-hospital mortality included low birth weight (p=0.004), preterm delivery (p=0.022) and respiratory distress syndrome (RDS) (p=0.002). RDS showed an independent association with death in the hospital (adjusted HR: 3.39; 95% CI: 1.11 to 10.35). Newborns delivered at home or in an ambulance had a 2.90 times higher hazard of dying in the hospital (95% CI: 1.17 to 7.17) compared with those delivered at the hospital.Conclusions Addressing preterm birth, low birth weight and respiratory distress, along with promoting institutional deliveries, is crucial for reducing neonatal mortality rates in resource-limited settings like Bangladesh.